Intestinal nematode infection exacerbates experimental visceral leishmaniasis. (4th March 2019) - Classon, Cajsa; Feng, Xiaogang; Eidsmo, Liv; Nylén, Susanne
Summary: Leishmania donovani exposure often results in subclinical infection in immunocompetent individuals, and the factors dictating development of visceral leishmaniasis (VL) are not known. Infection with intestinal worms skew immunity towards type 2 and regulatory responses, thereby theoretically increases susceptibility to intracellular infections controlled by type 1 responses. Here we have tested how chronic infection with the intestinal nematode Heligmosomoides polygyrus affected immunity to a secondary infection with L donovani . We found that mice infected with H polygyrus displayed higher Leishmania burden in liver and spleen compared to worm‐free animals. This increased infectious load was accompanied by reduced leucocyte infiltration and nos2 transcription in livers and increased il4 and il10 transcription in spleens. Collectively, these data show that chronic infection with intestinal nematodes skew immune responses in a way that may favour development of VL.